Titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy and preparation method thereof

By adjusting the composition and preparation process of titanium carbon or titanium aluminum carbon intermediate alloys, the problem of uneven distribution of carbon elements in high-temperature titanium alloys is solved, and the stability of material performance and production efficiency are improved.

CN119800149APending Publication Date: 2025-04-11XIAN RARE METAL MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510001434.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the preparation of existing high-temperature titanium alloys, it is difficult to uniformly distribute carbon elements, resulting in uneven formation types and distribution states of carbide phases, affecting the stability of the final product performance.

Method used

Titanium carbon or titanium aluminum carbon intermediate alloy is used to adjust the components to have high homogenization characteristics, and the melting point and density are adjusted to be similar to titanium sponge to avoid the formation of high melting point carbides, and the uniform distribution of aluminum and carbon elements is ensured through low-temperature sintering process.

Benefits of technology

The uniform distribution of carbon elements is achieved, the smelting temperature and time is reduced, the production efficiency is improved, the stability of material performance is ensured, and material waste and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800149A_ABST
    Figure CN119800149A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-carbon or titanium-aluminum-carbon intermediate alloy for a high-temperature titanium alloy, the titanium-carbon or titanium-aluminum-carbon intermediate alloy comprises the following elements in percentage by mass: 0.05-0.70% of C, 0-6% of Al and the balance of Ti and inevitable impurities, in addition, the invention further provides a preparation method of the titanium-carbon or titanium-aluminum-carbon intermediate alloy for the high-temperature titanium alloy, and the preparation method comprises the following steps: 1, selecting raw materials; 2, mixing the powder; 3, biscuit forming; 4, sintering at low temperature; and 5, post-processing to obtain the titanium-carbon or titanium-aluminum-carbon intermediate alloy for the high-temperature titanium alloy. The titanium-carbon or titanium-aluminum-carbon intermediate alloy has the characteristics of uniform element distribution, no precipitation of high-melting-point carbides and low impurity content, the melting point and the density of the titanium-carbon or titanium-aluminum-carbon intermediate alloy are similar to those of sponge titanium, solid solution of carbon elements in an alpha-Ti matrix is realized through component control and low-temperature solid-phase sintering, and meanwhile, generation of the high-melting-point carbides is effectively inhibited, so that the titanium-carbon or titanium-aluminum-carbon intermediate alloy has a good application prospect. Therefore, the stability and the homogeneity in the high-temperature smelting process of the high-temperature titanium alloy are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of intermediate alloy preparation, and in particular relates to a titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy and a preparation method thereof. Background Art

[0002] With the development of high-temperature titanium alloys, the role of carbon has changed significantly. In the early days (1950s), carbon was regarded as a harmful impurity in titanium and its alloys. Although a small amount of addition (up to 0.5wt.%) can enhance the strength and hardness of the material, its significant negative impact on plasticity prompted researchers to strictly limit its content, together with other interstitial elements (oxygen, nitrogen, hydrogen) to less than 0.2wt.%. Entering the 21st century, especially in the field of aerospace, carbon has been re-evaluated and regarded as a candidate to replace traditional expensive alloying elements due to its low cost, easy access and light weight, as well as its potential economic benefits and performance improvement. Microstructural analysis shows that carbon has a significant effect on the phase transformation process and lattice parameters of titanium alloys, can effectively inhibit excessive grain growth, and induce additional hardening effects during heat treatment. In terms of mechanical properties, the addition of an appropriate amount of carbon can significantly improve the tensile strength, yield strength and hardness of titanium alloys, while having a relatively small negative impact on impact strength. In addition, carbon also shows the ability to enhance the creep resistance, oxidation resistance and wear resistance of titanium alloys, and can significantly reduce the creep rate, oxidation rate and friction coefficient. However, it is worth noting that even at low concentrations, carbon may have an adverse effect on the plasticity of titanium alloys. Therefore, in practical applications, the carbon content in titanium alloys is usually strictly limited to 0.02 ~ 0.10 wt.%. Taking the high-temperature titanium alloys IMI834, TG6 and Ti65 used in aircraft engines as examples, the carbon content in their nominal composition is controlled at 0.05wt.%~0.06wt.%. In summary, carbon is a key element for optimizing the performance of titanium alloys. While it is strategically added, its content still needs to be strictly controlled to ensure that the comprehensive performance of the alloy is optimized.

[0003] At present, the preparation of high-temperature titanium alloys widely adopts the three-stage vacuum consumable arc melting process, in which the introduction of carbon is usually achieved by adding carbon elements, such as carbon black, carbon powder, etc. However, this method also faces specific challenges: (1) Mixing uniformity challenge: Since carbon powder accounts for a small volume and has a low density, during the mixing process of raw materials, carbon powder tends to float above other metal particles or accumulate in hidden corners of the barrel, making it difficult to ensure the uniform distribution of carbon elements in the entire raw material system; (2) Segregation and agglomeration problems during the melting process: Since the density of carbon is much lower than that of molten titanium (density is about 4.11g / cm 3), and its high melting point keeps carbon in a solid phase during the melting process. Therefore, during vacuum consumable arc melting, carbon tends to gather at the top of the molten pool due to density differences, which in turn may lead to uneven distribution of carbides in the ingot. In order to solve the above problems and ensure the effective introduction and uniform distribution of carbon elements, thereby improving the overall quality of high-temperature titanium alloy ingots, carbon-containing intermediate alloys for high-temperature titanium alloys have become a research hotspot and development trend. Among them, titanium-aluminum-carbon intermediate alloys are regarded as key alloy systems that meet the application needs of high-temperature titanium alloys because of their advantages such as similar melting point, density and higher carbon solid solubility (about 0.7wt.%) to sponge titanium.

[0004] For the preparation of titanium aluminum carbon master alloy, the application numbers are 200710016306.6, 00123953.8, 202110517615.1, 201710568449.1, 201811103620.2, 201910625528.0, 98119377.3, 02156761.1, 200410103904.3 and 20151016638 0.0, successively disclosed and improved methods for preparing titanium aluminum carbon master alloys based on melt-solidification technology. In this method, the melt needs to pass through the β-Ti phase and carbide two-phase region during cooling from a temperature above 1300°C to room temperature. Due to the low solubility of carbon in the β-Ti phase and the high diffusion rate of carbon at high temperature, it is very easy to cause a large amount of carbides to be generated. These methods cover melt reaction method, self-propagating high temperature synthesis method and thermal explosion synthesis method. However, in the titanium aluminum carbon master alloys prepared by the above patents, the content of Al and C is generally high. Under the joint action of thermodynamic and kinetic mechanisms, high melting point TiC or Al4C3 phases will inevitably form during the solidification process of the alloy. These high melting point carbide phases, when added to high temperature titanium alloys through master alloys, will lead to uneven formation type and distribution state of carbide phases, thereby causing fluctuations in the performance of the final product.

[0005] In the existing patents, the titanium-aluminum-carbon intermediate alloy is mainly used as a refiner, which promotes heterogeneous nucleation through the uniform distribution of TiC particles in the alloy matrix, and utilizes the "pinning effect" to limit the movement of grain boundaries during grain growth, thereby inhibiting the abnormal growth of grains. In view of this, there is an urgent need to develop a titanium-carbon or titanium-aluminum-carbon intermediate alloy and a preparation process thereof that has a significantly different composition from the titanium-carbon or titanium-aluminum-carbon intermediate alloy in the prior art. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy in view of the deficiencies of the above-mentioned prior art. The titanium-carbon or titanium-aluminum-carbon master alloy has high homogenization characteristics by adjusting the composition, does not contain high-melting-point carbides and has low impurity content. As an additive for the preparation of high-temperature titanium alloy, it not only reduces the smelting temperature and shortens the smelting time, but also contributes to the uniform distribution of carbides in the high-temperature titanium alloy, minimizes the segregation of carbon elements, ensures the performance stability of the material, and can also improve production efficiency and alloy yield, reduce material waste and reduce production costs.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy, characterized in that the titanium-carbon or titanium-aluminum-carbon intermediate alloy is composed of the following elements in mass percentage: C 0.05%~0.70%, Al 0%~6%, and the remainder is Ti and unavoidable impurities.

[0008] The above-mentioned titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy is characterized in that the mass percentage of each element in the inevitable impurities satisfies: Fe≤0.16%, Si≤0.10%, Mn≤0.06%, Mg≤0.06%, Cl≤0.08%, O≤0.30%, N≤0.10%, and H≤0.04%.

[0009] The titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy is characterized in that the melting point of the titanium-carbon or titanium-aluminum-carbon master alloy is 1650°C to 1670°C and the density is 4.30 g·cm -3 ~4.50g·cm -3 .

[0010] The present invention provides a titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloys, which takes Ti as a matrix and Al, C or C as a main alloying element. By adjusting the content of each component, a single HCP phase consisting of Ti, Al and C or Ti and C can be formed within a set alloy composition range. Compared with single carbon, the titanium-carbon or titanium-aluminum-carbon master alloy has a melting point of 1650°C to 1670°C and a density of 4.30 g·cm -3 ~4.50g·cm -3, which is similar to the melting point and density of sponge titanium. This property not only meets the demand of high-melting-point components for the addition of high-temperature titanium alloys, but also effectively solves the metallurgical problems of easy segregation and refractory melting of elemental carbon in the smelting process of high-temperature titanium alloys; in addition, the titanium-carbon or titanium-aluminum-carbon intermediate alloy of the present invention also exhibits good processing performance, which is convenient for subsequent cold drawing and cutting. The cut titanium-carbon or titanium-aluminum-carbon intermediate alloy particles can be used as raw materials and can be conveniently added in the smelting preparation process of high-temperature titanium alloys, which not only improves production efficiency but also enhances the convenience of operation.

[0011] In addition, the present invention also provides a method for preparing a titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy, characterized in that the method comprises the following steps: Step 1, raw material selection: select titanium powder, aluminum powder and carbon powder as raw materials or select titanium powder and carbon powder as raw materials, and place them in a vacuum oven for vacuum drying to obtain dried raw materials; Step 2: Mixing powder: placing the dried raw material and dispersant obtained in step 1 in a mixer and mixing them evenly to obtain a mixed powder; Step 3: green blank molding: the mixed powder obtained in step 2 is placed in a mold, then vacuum-packed, and then pressed in a cold isostatic press to obtain a green blank; Step 4, low temperature sintering: placing the green blank obtained in step 3 in a vacuum graphite sintering furnace at 850°C to 1050°C for 3h to 5h, and then cooling to room temperature with the furnace to obtain a sintered alloy; Step 5, post-processing: turning the sintered alloy obtained in step 4 to obtain titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy.

[0012] The present invention Figures 1 to 3 The sintering process was designed based on the calculated phase diagram of Ti-C binary alloy shown in the figure, the influence curve of Al addition on the maximum solid solubility of C in Ti, and the influence curve of Al addition on the phase transition temperature of Ti alloy containing C. Figure 2 The two lines represent the solid solubility of carbon in Ti matrices with different crystal structures. α-Ti presents an HCP (hexagonal close-packed) structure, which is the low-temperature stable phase of titanium; while β-Ti presents a BCC (body-centered cubic) structure, which is the high-temperature stable phase of Ti. The horizontal axis represents the amount of Al added to the system, and the vertical axis represents the maximum solid solubility of C element in the corresponding crystal structure and composition system after adding the corresponding Al content in different crystal structures. This figure mainly shows the effect of Al content on the solid solubility of carbon in the system, which is used to determine the optimal composition. Figure 3The two lines represent the temperature corresponding to the maximum solid solubility of carbon in the Ti matrix with different crystal structures. The horizontal axis represents the amount of Al added to the system, and the vertical axis represents the temperature required for the C element to reach the maximum solid solubility in the corresponding crystal structure and composition system after adding the corresponding Al content in different crystal structures. This figure is intended to be used to determine the optimal temperature conditions when preparing alloys to achieve the maximum solid solubility of carbon, such as Figures 1 to 3 As shown, when Al element is not added to the system, the maximum solid solubility of carbon in BCC phase β-Ti is about 0.15wt% (corresponding to a temperature of 1648°C), while the maximum solid solubility in HCP phase α-Ti can reach about 0.40wt% (corresponding to a temperature of 920°C). In view of this, in order to ensure that carbon has a higher solid solubility in titanium, the HCP phase structure of the matrix titanium needs to be maintained. Furthermore, with the introduction of Al element, the maximum solid solubility of carbon in α-Ti will increase accordingly, and the transformation temperature of the α-β phase will also increase. Based on this finding, the present invention sets the sintering temperature of the titanium aluminum carbon intermediate alloy to 850°C~1050°C. Within this temperature range, through the liquid phase mass transfer of aluminum and the solid phase diffusion mechanism of carbon, not only the sintering forming of the alloy can be achieved, but also the uniform distribution of aluminum and carbon elements in the titanium matrix can be ensured, thereby ensuring the dense sintering while avoiding the formation of a large amount of carbides.

[0013] The above method is characterized in that the mass purity of the titanium powder, aluminum powder and carbon powder in step 1 is greater than 99.5%, the particle size of the titanium powder is not greater than 400μm, the particle size of the aluminum powder is not greater than 200μm, and the particle size of the carbon powder is not greater than 80μm. The present invention significantly reduces the impurity content in the titanium-carbon or titanium-aluminum-carbon intermediate alloy by strictly controlling the mass purity of the raw materials titanium powder, aluminum powder and carbon powder, thereby ensuring the high purity of the titanium-carbon or titanium-aluminum-carbon intermediate alloy; by controlling the particle size of the titanium powder, aluminum powder and carbon powder, it ensures that the sintered alloy after sintering can achieve complete densification, and at the same time shortens the diffusion path of the carbon powder, increases the diffusion rate, so as to ensure the complete solid solution of carbon, effectively avoiding the formation of high-melting point carbides caused by local element aggregation, and then forming insufficient precipitation of carbides.

[0014] The above method is characterized in that the temperature of the vacuum drying in step 1 is 120°C to 160°C and the time is 8h to 12h. The present invention prevents the formation of a dense oxide layer on the surface of the titanium powder by controlling the parameters of the vacuum drying, and avoids the deficiency that the oxide layer hinders the diffusion of carbon into the titanium during the subsequent sintering process. The vacuum drying process effectively reduces the boiling point of water by reducing the environmental pressure, thereby improving the drying efficiency, and solving the problem that high-temperature drying in an atmospheric environment easily leads to material damage and alloy oxidation, so as to ensure the dryness of the raw materials.

[0015] The above method is characterized in that the particle sizes of the titanium powder, aluminum powder and carbon powder in step 2 satisfy: ,in, , and are the particle sizes of titanium powder, aluminum powder and carbon powder respectively. , and are the mass percentages of titanium powder, aluminum powder and carbon powder, respectively. , and The density of titanium powder, aluminum powder and carbon powder are respectively. The present invention determines the particle size of titanium powder and then calculates the appropriate particle size of aluminum powder and carbon powder, and finely controls the particle size ratio of the three powders through a formula, which effectively promotes the full fusion and uniform distribution of titanium powder, aluminum powder and carbon powder in the mixing process. In the powder mixing stage, the particle size difference, density distribution and content ratio between the powders have an important influence on the mixing uniformity. Based on the extensive practical experience in the field of powder mixing, when the product of the particle size, density and content of each powder tends to be consistent, better mixing uniformity can often be obtained. Therefore, reasonably setting and optimizing the particle size ratio of titanium powder, aluminum powder and carbon powder plays an important role in improving the performance and quality of the final product, ensuring that the density of the blank reaches the highest possible level when the blank is pressed. In the subsequent sintering process, when the sintering temperature and time are kept consistent, the higher the density of the blank, the higher the density of the sample obtained after sintering.

[0016] The above method is characterized in that the mixer in step 2 is a double-motion mixer, the loading amount of the double-motion mixer is 60% to 80%, the rotation speed for uniform mixing is not more than 20r / min, the time is not less than 2h, and the dispersant is ethanol. In the present invention, since the density of carbon powder is much smaller than that of Ti and Al, and the carbon powder particle size is relatively small, if a traditional double-motion mixer is used for mixing, the carbon powder is prone to aggregation, which may lead to agglomeration and caking, resulting in uneven mixing. By using a double-motion mixer and combining the loading amount, rotation speed and time, the problem of mixing fine and light carbon powder is solved, the uniformity and stability of mixing are ensured, and there is no agglomeration phenomenon, and the loading amount is less than 60%, which cannot effectively play a stirring role, and the loading amount exceeds 80%, the powder will lack sufficient space for effective mixing movement. In order to ensure the mixing effect and efficiency, the barrel of the double-motion mixer is filled to 60% to 80% of the capacity to compress the floating space of the light-weight and small-particle carbon powder during the mixing process. In addition, the double-motion mixer The movement speed is set at no more than 20r / min and the time is no less than 2h. This low-speed operation mode not only reduces the possibility of carbon powder flying due to mechanical force, but also ensures that the floating carbon powder can be efficiently entrained into the titanium powder and aluminum powder under the synergistic effect of the rotation of the barrel and the forced stirring of the blades, thereby achieving uniform mixing of the powders. By adding ethanol as a dispersant, the addition of ethanol can effectively penetrate and evenly distribute between the carbon powder and the titanium powder and aluminum powder, which helps to break the agglomeration between the particles, thereby preventing the agglomeration of the powder during the mixing process. At the same time, the rapid volatility of ethanol ensures that it will not remain in the powder after the mixing is completed, and will not have an adverse effect on the subsequent powder processing steps (such as pressing and sintering), effectively avoiding the potential impact of organic residues on material purity.

[0017] The above method is characterized in that the mold in step 3 is a rubber mold, the pressing pressure is 220MPa-250MPa, and the holding time is 15min-20min. The present invention adopts a rubber mold because of its good flexibility and elasticity, which can evenly transmit pressure, and combines the pressing parameters to ensure that the density of the pressed blank is uniform and the structure is dense.

[0018] The above method is characterized in that the removal thickness of the turning process in step 5 is 0.5 mm to 1 mm. The present invention controls the removal thickness of the turning process to remove the oxide layer or nitride layer with a thickness of 0.5 mm to 1 mm on the surface of the sintered alloy, thereby improving the performance of the titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloys.

[0019] Compared with the prior art, the present invention has the following advantages: 1. The present invention adjusts the composition of the traditional titanium-carbon or titanium-aluminum-carbon master alloy so that the provided titanium-carbon or titanium-aluminum-carbon master alloy can serve the smelting process of high-temperature titanium alloys. In particular, the melting point and density of the titanium-carbon or titanium-aluminum-carbon master alloy are adjusted to be close to those of sponge titanium to avoid the formation of high-melting point TiC or Al4C3 phases, so as to ensure stability and homogeneity in the high-temperature smelting process of high-temperature titanium alloys.

[0020] 2. The present invention deeply analyzes the Ti-C binary system or the Ti-Al-C ternary system from the perspective of thermodynamics, designs the alloy composition and preparation process, and finally successfully prepares a titanium-carbon or titanium-aluminum-carbon intermediate alloy composed of a single HCP phase, without the generation of high-melting point carbides, and with complete solid solution and uniform distribution of aluminum and carbon elements.

[0021] 3. The present invention discloses a preparation process of titanium-carbon or titanium-aluminum-carbon intermediate alloy by low-temperature sintering in the α-Ti single-phase region of 850°C to 1050°C. Within this temperature range, carbon has a higher solid solubility in the α-Ti phase, and the solid solution process of carbon and aluminum elements is mainly achieved through liquid phase mass transfer of aluminum and solid phase mass transfer of carbon. In this process, the diffusion rates of carbon and aluminum elements are moderate. By extending the sintering time, the complete solid solution of carbon and aluminum can be ensured. In the subsequent cooling process, the diffusion rates of carbon and aluminum elements will be further reduced. Although from a thermodynamic point of view, there is a tendency for carbide formation, due to its low diffusion rate, there is not enough time condition kinetically to form a large amount of high-melting point carbide phases such as TiC or Al4C3.

[0022] 4. The present invention realizes alloying and promotes the uniform distribution of aluminum and carbon elements in the titanium matrix through the aluminum liquid phase mass transfer and carbon solid phase mass transfer mechanism during the low-temperature sintering process. At the same time, the low-temperature sintering technology is used to effectively inhibit the formation of high-temperature carbides. Compared with the disclosed melt-solidification preparation method, the titanium aluminum carbon intermediate alloy prepared by low-temperature sintering technology has the advantages of uniform component distribution and no high melting point carbide formation, and is also suitable for large-scale production.

[0023] 5. The present invention implements strict control over the impurity content of the raw materials and the preparation process of the titanium-aluminum-carbon intermediate alloy, ensuring that the impurity content in the titanium-aluminum-carbon intermediate alloy is at an extremely low level. In the prepared titanium-aluminum-carbon alloy, titanium, aluminum, and carbon elements are evenly distributed without segregation, and there is no high-melting point carbide. Ultimately, the intermediate alloy product provides quality assurance for downstream materials of high-temperature titanium alloys and significantly improves the yield of the alloy.

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Calculated phase diagram of Ti-C binary alloy.

[0026] Figure 2 This is the curve showing the effect of Al addition on the maximum solid solubility of C in Ti.

[0027] Figure 3 This is the curve showing the effect of Al addition on the phase transition temperature of C-containing Ti alloy.

[0028] Figure 4 This is a SEM image of the Ti-1Al-0.5C master alloy prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] Example 1 This embodiment is for preparing Ti-0.05C master alloy.

[0030] This embodiment includes the following steps: Step 1, raw material selection: select titanium powder with a mass purity greater than 99.5% and a particle size of 150 μm and carbon powder with a mass purity greater than 99.5% and a particle size of 15 μm as raw materials according to Ti-0.05C, and place them in a vacuum oven at 150°C for vacuum drying for 10 hours; Step 2, powder mixing: Place the dried raw material obtained in step 1 and ethanol in a double-motion mixer with a loading amount of 70% and mix them evenly at a speed of 20 r / min for 2 hours to obtain a mixed powder; Step 3, green blank molding: the mixed powder obtained in step 2 is loaded into a rubber mold, and then vacuum-packed, and then placed in a cold isostatic press at a pressure of 250 MPa for 15 minutes to obtain a green blank; Step 4, low temperature sintering: placing the green blank obtained in step 3 in a vacuum graphite sintering furnace with a vacuum degree of 0.01 Pa, sintering at 850°C for 3 hours, and then cooling to room temperature with the furnace to obtain a sintered alloy; Step 5, post-processing: The sintered alloy obtained in step 4 is turned to remove a thickness of 0.5 mm to 1 mm to obtain a Ti-0.05C master alloy for high-temperature titanium alloy.

[0031] The Ti-0.05C master alloy prepared in this example was subjected to composition analysis, and the results are shown in Table 1.

[0032] Table 1

[0033] It can be seen from Table 1 that the Ti-0.05C master alloy prepared in this embodiment has titanium and carbon as main elements, and their contents are well controlled. More importantly, the contents of various impurity elements are at a relatively low level. This result fully proves that the low-temperature sintering process adopted in the present invention can effectively control the content of impurity elements, thereby ensuring the high purity of the alloy and the excellent quality of the final product.

[0034] After testing, the Ti-0.05C master alloy prepared in this embodiment meets the melting point of 1650℃~1670℃ and the density of 4.30g·cm -3 ~4.50g·cm -3 The Ti-0.05C intermediate alloy prepared in this embodiment does not have macroscopically visible carbide precipitation. When the Ti-0.05C intermediate alloy prepared in this embodiment is used for the preparation of high-temperature titanium alloy, the melting temperature is lowered, the melting time is shortened, and it is more conducive to the uniform distribution of carbides in the high-temperature titanium alloy, which minimizes the segregation of carbon elements, ensures the performance stability of the material, and obtains a high-temperature titanium alloy with uniform composition.

[0035] Example 2 This embodiment is for preparing Ti-1Al-0.5C master alloy.

[0036] This embodiment includes the following steps: Step 1, raw material selection: select titanium powder with a mass purity greater than 99.5% and a particle size of 150μm, aluminum powder with a mass purity greater than 99.5% and a particle size of 40μm, and carbon powder with a mass purity greater than 99.5% and a particle size of 30μm as raw materials according to Ti-1Al-0.5C, and place them in a vacuum oven at 120°C for vacuum drying for 12h; Step 2, powder mixing: Place the dried raw material obtained in step 1 and ethanol in a double-motion mixer with a loading amount of 60% and mix them evenly at a speed of 20 r / min for 2 hours to obtain a mixed powder; Step 3, green blank molding: the mixed powder obtained in step 2 is loaded into a rubber mold, and then vacuum-packed, and then placed in a cold isostatic press at a pressure of 230 MPa for 18 minutes to obtain a green blank; Step 4, low temperature sintering: placing the green blank obtained in step 3 in a vacuum graphite sintering furnace with a vacuum degree of 0.01 Pa, sintering at 900°C for 4 hours, and then cooling to room temperature with the furnace to obtain a sintered alloy; Step 5, post-processing: The sintered alloy obtained in step 4 is turned to remove a thickness of 0.5 mm to 1 mm to obtain a Ti-1Al-0.5C master alloy for high-temperature titanium alloy.

[0037] Figure 4The SEM image of the Ti-1Al-0.5C master alloy prepared in this embodiment is shown in FIG. Figure 4 It can be seen that no macroscopic carbide precipitation was observed in the Ti-1Al-0.5C intermediate alloy prepared in this embodiment, which fully verifies that the low-temperature sintering preparation process adopted by the present invention can effectively inhibit the formation of carbides, ensure the stable existence of the solid solution phase, and promote the uniform distribution of aluminum and carbon elements.

[0038] The Ti-1Al-0.5C master alloy prepared in this example was subjected to composition analysis. The results are shown in Table 2.

[0039] Table 2

[0040] As can be seen from Table 2, the titanium, aluminum and carbon in the Ti-1Al-0.5C master alloy prepared in this embodiment are the main elements, and their contents are effectively controlled. More importantly, the content of each impurity element is maintained at a relatively low level. This result further confirms that the preparation process adopted by the present invention can effectively control the content of impurity elements while maintaining the stability of the solid solution phase, thereby ensuring the high purity of the alloy and the excellent quality of the final product.

[0041] After testing, the Ti-1Al-0.5C master alloy prepared in this embodiment meets the melting point of 1650℃~1670℃ and the density of 4.30g·cm -3 ~4.50g·cm -3 In accordance with the requirements, when the Ti-1Al-0.5C intermediate alloy prepared in this embodiment is used for the preparation of high-temperature titanium alloy, the melting temperature is lowered, the melting time is shortened, and it is more conducive to the uniform distribution of carbides in the high-temperature titanium alloy, thereby minimizing the segregation of carbon elements, ensuring the performance stability of the material, and obtaining a high-temperature titanium alloy with uniform composition.

[0042] Example 3 This embodiment is for preparing Ti-6Al-0.7C master alloy.

[0043] This embodiment includes the following steps: Step 1, raw material selection: select titanium powder with a mass purity greater than 99.5% and a particle size of 150μm, aluminum powder with a mass purity greater than 99.5% and a particle size of 70μm, and carbon powder with a mass purity greater than 99.5% and a particle size of 35μm as raw materials according to Ti-6Al-0.7C, and place them in a vacuum oven at 160°C for vacuum drying for 8h; Step 2, powder mixing: Place the dried raw material obtained in step 1 and ethanol in a double-motion mixer with a loading amount of 80% and mix them evenly at a speed of 20 r / min for 2 hours to obtain a mixed powder; Step 3, green blank molding: the mixed powder obtained in step 2 is loaded into a rubber mold, and then vacuum-packed, and then placed in a cold isostatic press at a pressure of 220 MPa for 20 minutes to obtain a green blank; Step 4, low temperature sintering: placing the green blank obtained in step 3 in a vacuum graphite sintering furnace with a vacuum degree of 0.01 Pa, sintering at 1050°C for 3 hours, and then cooling to room temperature with the furnace to obtain a sintered alloy; Step 5, post-processing: The sintered alloy obtained in step 4 is turned to remove a thickness of 0.5 mm to 1 mm to obtain a Ti-6Al-0.7C master alloy for high-temperature titanium alloy.

[0044] The Ti-6Al-0.7C master alloy prepared in this example was subjected to composition analysis, and the results are shown in Table 3.

[0045] Table 3

[0046] It can be seen from Table 3 that the Ti-6Al-0.7C master alloy prepared in this embodiment has titanium, aluminum and carbon as main elements, and their contents are well controlled. More importantly, the contents of various impurity elements are at a relatively low level. This result fully proves that the low-temperature sintering process adopted in the present invention can effectively control the content of impurity elements, thereby ensuring the high purity of the alloy and the excellent quality of the final product.

[0047] After testing, the Ti-6Al-0.7C master alloy prepared in this embodiment meets the melting point of 1650℃~1670℃ and the density of 4.30g·cm -3 ~4.50g·cm -3 In accordance with the requirements, no macroscopic carbide precipitation was observed in the Ti-6Al-0.7C intermediate alloy prepared in this embodiment. When the Ti-6Al-0.7C intermediate alloy prepared in this embodiment is used for the preparation of high-temperature titanium alloy, the melting temperature is lowered, the melting time is shortened, and it is more conducive to the uniform distribution of carbides in the high-temperature titanium alloy, which minimizes the segregation of carbon elements, ensures the performance stability of the material, and obtains a high-temperature titanium alloy with uniform composition.

[0048] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy, characterized in that: The titanium-carbon or titanium-aluminum-carbon master alloy is composed of the following elements in percentage by mass: C 0.05%-0.70%, Al 0%-6%, and the remainder being Ti and unavoidable impurities.

2. The titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy according to claim 1, characterized in that: The mass percentage of each element in the inevitable impurities satisfies: Fe≤0.16%, Si≤0.10%, Mn≤0.06%, Mg≤0.06%, Cl≤0.08%, O≤0.30%, N≤0.10%, and H≤0.04%.

3. The titanium-carbon or titanium-aluminum-carbon master alloy for high-temperature titanium alloy according to claim 1, characterized in that: The melting point of the titanium-carbon or titanium-aluminum-carbon master alloy is 1650° C. to 1670° C., and the density is 4.30 g·cm -3 ~4.50g·cm -3 .

4. A method for preparing a titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloys as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1, raw material selection: select titanium powder, aluminum powder and carbon powder as raw materials or select titanium powder and carbon powder as raw materials, and place them in a vacuum oven for vacuum drying to obtain dried raw materials; Step 2: Mixing powder: placing the dried raw material and dispersant obtained in step 1 in a mixer and mixing them evenly to obtain a mixed powder; Step 3: green blank molding: the mixed powder obtained in step 2 is placed in a mold, then vacuum-packed, and then pressed in a cold isostatic press to obtain a green blank; Step 4, low temperature sintering: placing the green blank obtained in step 3 in a vacuum graphite sintering furnace at 850°C to 1050°C for 3h to 5h, and then cooling to room temperature with the furnace to obtain a sintered alloy; Step 5, post-processing: turning the sintered alloy obtained in step 4 to obtain titanium-carbon or titanium-aluminum-carbon intermediate alloy for high-temperature titanium alloy.

5. The method according to claim 4, characterized in that The mass purity of the titanium powder, aluminum powder and carbon powder in step 1 is greater than 99.5%, the particle size of the titanium powder is not greater than 400 μm, the particle size of the aluminum powder is not greater than 200 μm, and the particle size of the carbon powder is not greater than 80 μm.

6. The method according to claim 4, characterized in that The vacuum drying in step 1 is carried out at a temperature of 120°C to 160°C and for a time of 8h to 12h.

7. The method according to claim 4, characterized in that The particle sizes of the titanium powder, aluminum powder and carbon powder in step 2 satisfy: ,in, , and are the particle sizes of titanium powder, aluminum powder and carbon powder respectively. , and are the mass percentages of titanium powder, aluminum powder and carbon powder, respectively. , and are the densities of titanium powder, aluminum powder and carbon powder respectively.

8. The method according to claim 4, characterized in that The mixer in step 2 is a double-motion mixer, the loading amount of the double-motion mixer is 60% to 80%, the speed of the uniform mixing is not greater than 20r / min, the time is not less than 2h, and the dispersant is ethanol.

9. The method according to claim 4, characterized in that The mold in step three is a rubber mold, the pressing pressure is 220MPa~250MPa, and the holding time is 15min~20min.

10. The method according to claim 4, characterized in that The removal thickness of the turning process described in step 5 is 0.5mm~1mm.

Citation Information

Patent Citations

  • Method for preparing aluminium-titanium-carbon master alloy

    CN100467635C

  • Aluminum titanium carbon intermediate alloy refinement agent and preparation technology thereof

    CN104894417A

  • Preparation method of Al-Ti-C intermediate alloy

    CN107354330A

  • A method for preparing Al-Ti-C master alloy

    CN109055792B

  • A method for rapid preparation of titanium aluminum carbon ceramics at room temperature

    CN110357633B

Cited By

  • Al-tic intermediate alloy with high tic content and preparation method thereof

    CN122669256A